(untitled) (Eurasian Journal of Research, Development and Innovation, 2024)
During the research, aluminum oxide nanoparticles were prepared by co-precipitation method using aluminum sulphate and sodium hydroxide base. A white precipitate was obtained, which is aluminum hydroxide gibbsite. After drying, this product was exposed to two different temperatures (600 and 1000°C) for the purpose of obtaining aluminum oxides and studying the effect of calcination temperature on the properties and phase of Infrared spectroscopy, X-ray diffraction, and scanning electron .the resulting oxides microscopy were used to diagnose the resulting oxides and determine their properties. The peaks formed in the FTIR spectrum confirmed the formation of the oxide Al2O3, while the The scanning electron microscope images that showed the surface morphology showed the formation of spherical and cylindrical shapes of irregular size and large aggregates that became more regular and less aggregated when the temperature was The effectiveness of the prepared oxides in removing reactive blue 4 .raised to 1000°C dye using the adsorption method was compared under different conditions, such as the effect of surface weight, the effect of dye concentration, as well as the effect of shaking time. It was found that the oxide prepared at 600°C was more effective in removing the dye. This confirms the possibility of its use in removing contaminated organic dyes from polluted water